Menjadi Ibu Tiri untuk Anak Cerebral Palsy - Astuti, Diah (INKLUSI, 2019)
This study aims to determine how the experience of being a good stepmother for children with cerebral palsy (CP children). With the stigma of a stepmother who tends to be negative, is it still possible to be a good stepmother for a CP child? In answering this question, the writer uses Talcot Parson’s functionalism-structuralist theory to see the fulfillment of certain conditions for the creation of a stable/harmonious family. Data collection is done by interview and observation techniques. This research concludes that stepmothers are not always bad, not ideal, or evil-tempered. The determinants of how a stepmother is accepted are inseparable from the background of her life and acceptance and support from the family, both the nuclear family or extended family. [Penelitian ini bertujuan untuk mengetahui bagaimana pengalaman menjadi ibu tiri yang baik bagi anak dengan cerebral palsy (anak CP). Dengan stigma ibu tiri yang cenderung negatif, masih mungkinkah menjadi ibu tiri yang baik bagi seorang anak CP? Dalam menjawab pertanyaan tersebut, penulis menggunakan teori fungsionalisme-strukturalis dari Talcot Parson untuk melihat pemenuhan syarat tertentu demi terciptanya keluarga yang stabil/harmonis. Pengumpulan data dilakukan dengan teknik wawancara dan observasi. Penelitian ini menyimpulkan bahwa ibu tiri tidak selalu buruk, tidak ideal, atau berperangai jahat. Adapun faktor penentu bagaimana ibu tiri diterima tidak terlepas dari latar belakang kehidupannya dan penerimaan dan dukungan dari keluarga, baik keluarga inti atau keluarga besar.]